Internet of things and pan-healthcares - Jianguo MA; Hengyue JIN (物联网学报)
The Internet of things is the result of the informatization.The purpose of the Internet of things is to let things speak.The health of both man’s body and the structures being used daily needs to talk urgently.A novel IoT architecture based on the deep machine-learning was proposed.The Internet of things through embedded depth learning,realizes the flow from the data stream to the streams of events,and then to the flow of knowledge the value stream.The core technology for IoT is prediction,protection and prevention.